INVESTIGATION OF THERMOMECHANICAL BEHAVIORS OF THE AGED ALLOYS $Ti55.68Ni44.32$ - Özkul, İskender; Canbay, Canan Aksu (My University, 2018)
TiNi alloys are used in places requiring precision jobs for the last few decades. Thermally induced shape memory alloys suchas TiNi are exposed to temperature cycle during the implementation, and the temperature causes an artificial aging effect onthe alloy. In this study, we aimed at investigating whether the aging effects depend on time and temperatures for TiNi alloys.Seven waiting periods with three different temperature values were applied. Totally 22 experiments were conducted, and theresults of the transformation temperatures were obtained for each experiment. Time depended results, especially for 200 °Csamples exhibited more stable state than 300 and 400 °C. When the temperature values are considered, a remarkable increaseis observed after 200 °C.
Keywords: Malzeme Bilimleri; Özellik ve Test; Fizikokimya